Janežičeva Slovenska slovnica 1854 - Toporišič, Jože (Slavistična revija, 1996)
Janežič's Slovene Grammar of 1854 is an interesting sketch of a simpler grammar written in Slovene and intended for high schools, based on the renowed scientific grammars by B. Kopitar (1808/9) and F. Metelko (1825). It relies considerably on Metelko's school grammar of 1830, in some respects on Miklošič's work (Janežič was in personal contact with both of them), and particulary with respect to terminology (to the lesser extent in theory) also on the grammars written in Slovene from the end of pre-March and from the beginning of the post-March era. The grammar Assumed its permanent from with its second edition of 1863.
Keywords: 19.st.; grammar; Janežič, Anton; Janežič, Anton: Slovenska slovnica; Slovene; slovenščina; slovnica; zgodovinski pregledi